2022
DOI: 10.3390/brainsci12070913
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus Accumbens Response to Reward among Children with a Family History of Alcohol Use Problems: Convergent Findings from the ABCD Study® and Michigan Longitudinal Study

Abstract: Having a family history of alcohol use problems (FH+) conveys risk for alcohol use in offspring. Reward-related brain functioning may play a role in this vulnerability. The present study investigated brain function in the nucleus accumbens (NAcc) associated with the anticipation of reward in youth with two biological parents with alcohol use problems (FH+2), one biological parent with alcohol use problems (FH+1), and no biological parents with alcohol use problems (FH-). Participants were from the large, natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Consistent with previous research (e.g., 18 , 48 , 49 ), our results indicate that those with positive family histories have less neural differentiation between rewarding and neutral cues and outcomes, than those without such family histories. These results suggest that the family history positive group has dampened monetary reward salience irrespective of unpredictable threat.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous research (e.g., 18 , 48 , 49 ), our results indicate that those with positive family histories have less neural differentiation between rewarding and neutral cues and outcomes, than those without such family histories. These results suggest that the family history positive group has dampened monetary reward salience irrespective of unpredictable threat.…”
Section: Discussionsupporting
confidence: 92%
“…For example, a study of children and adolescents showed that those with, relative to without, a family history of harmful alcohol use showed reduced activation in the nucleus accumbens when anticipating potential monetary rewards. 18 Similarly, greater synchrony of reward circuitry (including the accumbens) during early adolescence was a predictor of future risky drinking for females in a large longitudinal study. 19 Biological response to a threat of shock (i.e., strength of eye blink reflex) was stronger in young adults with, relative to without, a family history of AUD.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Earlier age of drinking onset is associated with alcohol dependence later in life (Grant, 1998) and psychopathology symptoms (Skogen et al, 2016). Children coming from a family with history of AUD are more likely to have reduced anticipatory reward responding (Martz et al, 2022), and reward sensitivity features can influence the degree of alcohol consumption across development (Watts et al, 2023). On the other hand, adolescents who are less likely to sip alcohol present higher self-esteem, behavioral regulation and increased liking of school (May et al, 2022).…”
Section: The Onset Of Alcohol Usementioning
confidence: 99%
“…Adolescence is an evolutionarily conserved period during which reward‐related behaviors, including social behaviors, develop via developmental plasticity in the mesolimbic dopaminergic “reward” circuitry of the brain (Brenhouse & Schwarz, 2016; Manduca et al., 2016). The nucleus accumbens (NAc) is an intermediate reward relay center that develops during adolescence (Bayassi‐Jakowicka et al., 2021; Huppe‐Gourgues & O'Donnell, 2012; Kopec et al., 2018; Martz et al., 2022; Orihuel et al., 2021) and mediates both social behaviors and dopaminergic signaling (Halbout et al., 2019; Manduca et al., 2016). In rodents, the NAc is particularly sensitive to social experience: Both positive and negative social experiences during adolescence produce long‐term effects in both the neuroanatomy of the NAc and matured social behaviors (Bendersky et al., 2021; Lemos et al., 2021).…”
Section: Introductionmentioning
confidence: 99%